Path Analysis of Healthy Cognitive Life Skills Effect on Children’s Self-Esteem, Knowledge, Critical Thinking, and Decision-Making Skills - Ratih Indraswari; Bagoes Widjanarko; Riza Hayati Ifroh (Fakultas Ilmu-ilmu Kesehatan, 2026)
Early engagement in risky sexual behavior among Indonesian adolescents is often associated with limited reproductive health knowledge and environmental factors. This study evaluated the effectiveness of a Healthy Cognitive Life Skills (HCLS) educational model using interactive games to improve children's reproductive health knowledge, self-esteem, critical thinking skills, decision-making skills, and attitude toward reproductive health. A quasi-experimental study with a non-equivalent control group pretest-posttest design was conducted among 254 children aged 9-10 years from two elementary schools in Semarang City, Indonesia. Data were collected using validated questionnaires and analyzed using partial least squares structural equation modeling (PLS-SEM). The HCLS educational model did not demonstrate a significant direct effect on cognitive life skills. However, it significantly improved self-esteem, which subsequently mediated improvements in reproductive health knowledge, critical thinking skills, and decision-making skills. The intervention did not directly improve attitudes toward reproductive health, although cognitive life skills and self-esteem were positively associated with attitudes. These findings suggest that game-based HCLS education primarily enhances children’s cognitive skills through strengthening self-esteem rather than through direct educational effects. Incorporating strategies that specifically target the affective domain may further improve attitudes toward reproductive health.